2014
DOI: 10.1371/journal.pone.0085010
|View full text |Cite
|
Sign up to set email alerts
|

Generation of “Virtual” Control Groups for Single Arm Prostate Cancer Adjuvant Trials

Abstract: It is difficult to construct a control group for trials of adjuvant therapy (Rx) of prostate cancer after radical prostatectomy (RP) due to ethical issues and patient acceptance. We utilized 8 curve-fitting models to estimate the time to 60%, 65%, … 95% chance of progression free survival (PFS) based on the data derived from Kattan post-RP nomogram. The 8 models were systematically applied to a training set of 153 post-RP cases without adjuvant Rx to develop 8 subsets of cases (reference case sets) whose obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…There are previous studies that have used different RWD sources to replicate the control arm from oncology RCTs. [28][29][30][31] Recently, Carrigan et al used electronic health record (EHR) data to derive control arms for 11 non-small cell lung cancer trials. 31 In 10 of the 11 RCTs, the OS HRs using the RWD comparator arm were similar to the HRs reported in the RCTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are previous studies that have used different RWD sources to replicate the control arm from oncology RCTs. [28][29][30][31] Recently, Carrigan et al used electronic health record (EHR) data to derive control arms for 11 non-small cell lung cancer trials. 31 In 10 of the 11 RCTs, the OS HRs using the RWD comparator arm were similar to the HRs reported in the RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…There are previous studies that have used different RWD sources to replicate the control arm from oncology RCTs 28–31 . Recently, Carrigan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Other research efforts for establishing ECs have also shown early promise. [19][20][21][22] Jia et al 22 examined an application in prostate cancer using a modeling approach based on existing trial data with reasonable success. Other studies drawing on aggregate findings from the clinical trial literature have been performed in acute myeloid leukemia 20 and anaplastic lymphoma kinase-targeted Figure 4 Estimates of relative risk across different adjustment methods comparing external control analysis to trial result: randomized controlled trial NCT0236143.…”
Section: Discussionmentioning
confidence: 99%
“…Jia et al [ 46 ] studied the effectiveness of adjuvant therapy for prostate cancer. Statistical models were generated to predict time of progression free survival with non adjuvant-treated patients.…”
Section: Main Textmentioning
confidence: 99%